Energy and exergy analyses of new cooling schemes based on a serpentine configuration for a high concentrator photovoltaic system. (25th November 2021) - Ahmed, Asmaa; Shanks, Katie; Sundaram, Senthilarasu; Mallick, Tapas
Highlights: A 3D computational model for a high concentrator photovoltaic system was built. New heat sink arrangements were investigated. A straight channel heat sink is not recommended above 1000 × . Using serpentine geometrical patterns reduced the solar cell temperature notably. Cell temperature varied from 95.5 ° C to 66 °C at 2000 × for serpentine arrangement. Abstract: High concentrator photovoltaic is expected to play an increasingly important role in electrical energy production. Controlling multijunction solar cell temperature within the recommended conditions is a key challenge that limits the functionality of this growing technology making the identification of an efficient cooling method an essential requirement. Hence, in this research, new heat sink configurations based on a serpentine design are studied and compared with the straight channel arrangement. To assess the performance of the high concentrator photovoltaic, a 3D model is built for the multijunction cell and heat sink and impact of the heat sink configuration, mass flow rate, and concentration ratio are investigated. The results include solar cell temperature distribution, thermal resistance, pumping power, thermal and electrical energy and exergy efficiencies. The study shows that the straight channel is not recommended for concentration above 1000 ×, whereas the centre inlet serpentine design can maintain a uniform temperature distribution for the system for concentration up to 2000 × . Temperature non-uniformity varies between 18 °C and 5 °C. The highest overall energy and exergy efficiencies reached 78% and 35.2% respectively at concentration of 2000 × . The results prove the effectiveness of implementing a serpentine design as a new cooling scheme for the system.